Bimetallic ruthenium–rhodium particles supported on carbon nanotubes for the hydrophosphinylation of alkenes and alkynes. Issue 16 (20th July 2022) - Jawale, Dhanaji V.; Fossard, Frédéric; Miserque, Frédéric; Geertsen, Valérie; Doris, Eric; Gravel, Edmond
Abstract : RuRh bimetallic particles supported on carbon nanotubes were applied to the hydrophosphinylation of alkenes and alkynes. This recyclable system operates under sustainable conditions: low catalyst loading, room temperature and atmospheric pressure. Abstract : Bimetallic ruthenium–rhodium nanoparticles were assembled on carbon nanotubes and applied to the hydrophosphinylation reaction of olefin and alkyne-containing compounds. The system proved efficient under mild and sustainable conditions, operating with low catalyst loading, at room temperature, and under atmospheric pressure. In addition, the catalytic hybrid could be recycled and reused over multiple cycles.